Identifikasi Prinsip Dasar Ekowisata di Desa Wisata Turgo-Merapi, Kabupaten Sleman - Fhikri Fratama; Eko Sugiarto (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
This study aims to identify five basic principles of ecotourism, namely conservation, education, recreation, economy, and community participation in Turgo-Merapi Tourism Village using qualitative methods. Primary data was obtained through uninvolved observation and semi-structured interviews with the community, tourism village managers, and actors of ecotourism activities in Turgo-Merapi Tourism Village. Secondary data was obtained from the study of relevant documents and data provided by the tourist village manager in the form of documentation of ecotourism activities. The results showed that the conservation principle was identified as the most dominant principle applied in almost all activities in Turgo-Merapi Tourism Village. The application of the principles of education, economy, recreation, and community participation still varies for each tourism activity. Therefore, efforts are needed to improve tourism education programs and economic empowerment based on local community participation. This study has limitations because it only identifies the basic principles of ecotourism as the results of the research. Further research should focus on examining the best strategies to strengthen the integration of conservation, economy, education, recreation, and community participation in the development of ecotourism-based tourism destinations. Thus, the development of ecotourism in Turgo-Merapi Tourism Village is expected to be sustainable and bring greater benefits to the community and the environment.